Difficult orotracheal intubation in a rabbit resulting from the presence of faecal pellets in the oropharynx. Issue 1 (2nd February 2016) - Engbers, Sarah; Larkin, Amy; Jonnalagadda, Mahesh; Prebble, Melanie; Rousset, Nicolas; Knight, Cameron G; Pang, Daniel S J
Abstract : Rabbits have a high rate of anaesthesia‐related death compared with other companion animal species. This is influenced by a variety of factors, one of which is difficulty in obtaining a secure airway. The rabbit in this report was enrolled in a larger non‐survival study that required orotracheal intubation to be performed. Orotracheal intubation was difficult, taking 306 seconds, compared with a median of 134 seconds (range 29–171 seconds) in the four preceding rabbits. Necropsy examination revealed a faecal pellet lodged in the caudal oropharynx abutting compacted faecal material, ventral to the epiglottis. Two structures of mixed gas and soft tissue attenuation were seen on CT scans obtained pre‐ and post‐intubation, at a location consistent with the faecal material, thus confirming the presence of the pellets at the time of sedation and during intubation. Oral prehension of faecal pellets before anaesthesia represents a previously unreported obstacle to orotracheal intubation in rabbits.